Cost assessment for 12-story medium-rise reinforced concrete residential building models in Sabah, considering seismic design - N. S., Zulkhibri; Mohd Irwan, Adiyanto (IOP Publishing Ltd, 2025)
On June 5th, 2015, the Ranau region experienced a notable seismic event with a magnitude, Mw 6.1. Hence, seismic designs shall be implemented to mitigate damage to structures, particularly in Sabah. The seismic designs increased the required steel reinforcement, which elevated the cost estimations of the building models. Therefore, this research investigated the impact of seismic designs on cost estimation at varying values of the reference peak ground acceleration (PGA), αgR. Phase 1 encompassed analysing and designing a non-seismic model of an irregularly 12-story reinforced concrete (RC), square-shaped residential building model utilising Tekla Structural Designer 2024 software followed by Eurocodes 1 and 2 (2004). Meanwhile, the details of the gravitational and wind actions were specified in the Malaysian National Annex to Eurocode 1 (2010) and the Malaysian Code of Practice on Wind Loading (2002), respectively. Phase 2 involved the re-analysed and re-designed to incorporate seismic provisions of Soil Type B and values of the reference PGA, αgR = 0.08g, 0.12g, and 0.16g, as outlined in Eurocode 8 (2004) and the Malaysian National Annex to Eurocode 8 (2017). Phase 3 calculated the take-off concrete volume, required steel reinforcement, and formwork area by comparing the seismic designs to the non-seismic building models. Thus, this study provided detailed information on cost estimations for the construction parties to construct a secure medium-rise irregularly building models during earthquakes, especially on 12-story building models. The results demonstrated that seismic designs increased the total estimation costs by -1.37% to 11.61% for PGA values, αgR, of 0.08g, 0.12g, and 0.16g, respectively.